INTERNALIZATION OF ISLAMIC EDUCATION IN THE TAMADUN MANDIRI PROGRAM IN THE ISLAMIC RELIGIOUS EDUCATION STUDY PROGRAM IN UNIVERSITAS PEMBANGUNAN PANCA BUDI MEDAN - Daud Kilau; Junaidi Arsyad; Azizah Hanum OK (UIN Sumatera Utara Medan, 2024)
This research aims to analyze the form of the program, implementation and results of the implementation of the internalization of Islamic education in the Tamadun Mandiri campus program. This research uses a qualitative method with a case study approach. This research uses three steps in collecting research data, namely: observation, interviews and documentation studies. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the research show that: the forms of internalization of Islamic education programs in the independent Tamadun campus program are: Koran village program, Al-Qur'an study program or thematic study of the Koran, workshop program and program to commemorate Islamic holidays. Furthermore, the process of implementing internalization is carried out through: learning and teaching activities in lecture rooms, commemorating Islamic holidays, studying Islamic knowledge, implementing a clean civilization culture. The results of internalizing Islamic education in the independent Tamadun campus program are: the formation of a culture of clean civilization, the formation of a love for Al-Qur'an knowledge, respecting and observing Islamic holidays, and the formation of a Koran village program.